Variability in Basal Melting Beneath Pine Island Ice Shelf on Weekly to Monthly Timescales - Davis, Peter E. D.; Jenkins, Adrian; Nicholls, Keith W.; Brennan, Paul V.; Abrahamsen, E. Povl; Heywood, Karen J.; Dutrieux, Pierre; Cho, Kyoung‐Ho; Kim, Tae‐Wan (Journal of Geophysical Research: Oceans, 2018)
Ocean-driven basal melting of Amundsen Sea ice shelves has triggered acceleration, thinning, and grounding line retreat on many West Antarctic outlet glaciers. Here we present the first year-long (2014) record of basal melt rate at sub-weekly resolution from a location on the outer Pine Island Ice Shelf. Adjustment of the upper thermocline to local wind forced variability in the vertical Ekman velocity is the dominant control on basal melting at weekly to monthly timescales. Atmosphere-ice-ocean surface heat fluxes or changes in advection of modified Circumpolar Deep Water play no discernible role at these timescales. We propose that during other years, a deepening of the thermocline in Pine Island Bay driven by longer timescale processes may have suppressed the impact of local wind forcing on high-frequency upper thermocline height variability and basal melting. This highlights the complex interplay between the different processes and their timescales that set the basal melt rate beneath Pine Island Ice Shelf.